The work of hospitals : global medicine in local cultures - Olsen, William C.; Sargent, Carolyn F., 1947- (New Brunswick : Rutgers University Press, 2022)
In the context of neoliberalism and global austerity measures, health care institutions around the world confront numerous challenges in attempting to meet the needs of local populations. Examples from Africa (including, Ethiopia, Ghana, and Congo), Latin America (Peru, Mexico, Guatemala), Western Europe (France, Greece), and the United States illustrate how hospitals play a significant role in the social production of health and disease in the communities where they are. Many low-resource countries have experienced increasing privatization and dysfunction of public sector institutions such as hospitals, and growing withdrawal of funding for non-profit organizations. Underlying the chapters in The Work of Hospitals is a fundamental question: how do hospitals function lacking the medications, equipment and technologies, and personnel normally assumed to be necessary? This collection of ethnographies demonstrates how hospital administrators, clinicians, and other staff in hospitals around the world confront innumerable risks in their commitment to deliver health care, including civil unrest, widespread poverty, endemic and epidemic disease, and supply chain instability. Ultimately, The Work of Hospitals documents a vast gulf between the idealized mission of the hospital and the implementation of this mission in everyday practice. Hospitals thus become "contested space" between policy and practice
Introduction / William C. Olsen and Carolyn Sargent -- Part One. Global Medicines in Local Cultures -- Chapter 1 Global Health Goals and Local Constraints in a Rural Peruvian Clinic / Morgan K. Hoke, Samya R. Stumo and Thomas L. Leatherman -- Chapter 2 Science and Sanctity: Biomedicine and Christianity at an Ethiopian Hospital / Anita Hannig -- Chapter 3 The Cosmopolitan Hospital / Cheryl Mattingly -- Chapter 4 "Dangerous Disease" Epilepsy in Asante / William C. Olsen -- Chapter 5 The Salience of the State in Biomedicine: Congo and Uganda Cases Compared / John M. Janzen-- Part Two. Care Giving and Hospital Labor -- Chapter 6 Creating a Therapeutic Community: Lessons from Allada Hospital Benin / Mark Nichter, Ghislain Emmanuel Sopoh and Roch Christian Johnson -- Chapter 7 Medical "Errands" among Women with Cervical Cancer in Guatemala / Anita Chary and Peter Rohloff -- Chapter 8 Routinized Caring or a "Call" to Nursing: Shifts in Hospital Nursing in Rukwa, Tanzania / Adrienne E. Strong -- Chapter 9 "We Work with What We Have, Not with What We Would Like to Have" Hospital Care in Mexico / Vania Smith-Oka and Kayla J. Hurd -- Part Three. Hospitals and the Patient -- Chapter 10 The Navigation of Public Hospitals by West African Immigrants with Cancer in Paris, France / Carolyn Sargent -- Chapter 11 Each Child Is Unique: The Responsible U.S. Parent's Take on Hospital Care Gone Wrong / Elisa J. Sobo -- Chapter 12 Making Ethnographic Sense of Cesarean Rates in Greek Public Hospitals / Eugenia Georges -- Chapter 13 The Nightside of Medicine: Obstetric Suffering and Ethnographic Witnessing in a Pakistani Hospital / Emma Varley -- Afterword / Claire Wendland -- References -- Notes on Contributors -- Index
Includes bibliographic references and index.
Description based on online resource, title from digital title page (viewed on June 21, 2024)
eBooks on EBSCOhost
Keywords: Hospitals; World health; Global Health; Santé mondiale; Hôpitaux.; hospitals (institutions, health facility); MEDICAL -- General; Hospitals; World health; Peru, Ethiopia, Congo, Ghana, Uganda, Benin, Guatemala, Tanzania, Mexico, France, The US, Greece, Pakistan, meidcine, hospitals; Electronic book